MO-DM Tool: Improving teams’ engagement with Motivation-Oriented Decision-Making - Barbosa Neto, Alvaro Magnum; Alvaro, Emmanuel; Bandeira, Marcílio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
A significant part of Software Engineering students’ academic and professional life involves working on projects in collaboration with their peers. They will form teams and perform on many software-related projects. Studies based on a systematic literature review and experimental results in a multidisciplinary tech-based innovation course with undergraduate students from Computer Engineering and Computer Science indicate difficulties in two significant activities in collaborative work: decision-making and reaching consensus. These recurrent difficulties negatively affect learners’ motivation and engagement throughout the project’s life cycle, besides other losses. This article aims to present a tool based on a model called MO-DM (Motivation-Oriented Decision-Making) proposed in doctoral research to address these hardships. It enables a new project view of members’ motivation and engagement, considering all the choices made along the project journey. The tool is grounded on EVC (Expectancy-Value-Cost) model, using it in a new way. Decisions like ”What programming language should we use?” are observed from the perspective of ”Which programming language can bring more engagement and motivation to the majority of the team?”. This view makes it possible to identify which students are more susceptible to being demotivated and disengaged in each step, and actions can be performed to mitigate these effects. Teams can make more engaging and motivating choices by picking the ones that will positively affect most of the group, enhancing the chances of successful projects. MO-DM tool is under preliminary tests with satisfactory results. Many decision-making situations where motivation and engagement are concerns can benefit from MO-DM. Tool presentation video link here.